A new Cyrtodactylus (Squamata: Gekkonidae) from Huong Son limestone forest, Hanoi, northern Vietnam - Luu, Vinh Quang; Nguyen, Truong Quang; Do, Huy Quang; Ziegler, Thomas (Zootaxa, 2011)
We describe a new species of the genus Cyrtodactylus based on two adult specimens from Huong Son limestone forest, Hanoi, Vietnam. Cyrtodactylus huongsonensis sp. nov. is distinguished from the remaining Indochinese bent-toed geckos by a combination of the following characters: medium-sized, with a maximum SVL of 89.8 mm; dorsal pattern consisting of dark nuchal loop, neck band and five in part irregular transverse body bands between limbs; two en-larged lateral chinshields in contact with first postmental pair; dorsal tubercles present on occiput, body, forearms, hind limbs and tail base; 14–16 irregularly running dorsal tubercle rows; ventrals in 41–48 longitudinal rows at midbody; lateral skin folds present, without interspersed tubercles; six precloacal pores plus in total 17 femoral pores in males, which are separated by 8–12 poreless scales; enlarged femoral scales and precloacal scales present; three postcloacal spurs in males; subcaudal scales transversely enlarged. This is the 24th species of Cyrtodactylus known from Vietnam.